QUALITATIVE AND QUANTITATIVE PHYTOCHEMICAL ANALYSIS AND BACTERICIDAL ACTIVITY OF PELARGONIUM GRAVEOLENS L’HER - Pradeepa, M.; Kalidas, V.; Geetha, N. (International Journal of Applied Pharmaceutics, 2016)
Objective: The present study investigates the qualitative and quantitative phytoconstituents and bactericidal effect of medicinally important Pelargonium graveolens L' Her leaves extracts. Methods: Preliminary phytochemical screening analyses were determined using standard protocol methods. In addition, antibacterial activities of the P. graveolens leaves extracts were evaluated by disc diffusion method against Gram-positive and Gram-negative bacteria. Results: The results revealed that ethanolic extract of P. graveolens was found to be the predominant occurrence of phytochemicals (9/11) which contains flavonoid, phenol, tannins, saponins, reducing sugar, glycosides, terpenoids, anthraquinone, and phlorotannins while starch and steroids were absent. In quantitative estimation of bioactive phytoconstituents showed carbohydrates (74 mg/gdw), protein (41.25 mg/gdw), chlorophyll (2.2Â±0.05 mg/gdw), lipids (0.07 mg/gdw), tannins (135.3 gm/gdw), phenolic compounds (123.75 mg/gdw) and flavonoids (50 mg/gdw) were found to have higher amount in ethanolic extract followed by acetone, methanol and aqueous extract and also showed an inhibitory action on growth of tested bacteria. Conclusion: Ethanolic extract of the P. graveolens leaves hold promises as a potential source of pharmaceutically important phytochemicals and also have strong antibacterial activity against Staphylococcus aureus, Escherichia coli, Pseudomonas aeroginosa and Klebsiella pneumonia. Keywords: Phytochemical screening, Primary and secondary metabolites, Antibacterial screening, Pelargonium graveolens